The role of pharmacists at the implementation of transformational leadership in the hospital central sterilization - Nugroho, Dwi Agung Nugroho; Kusuma, Aris Perdana (Jurnal Ilmiah Farmasi, 2024)
Background: Pharmacists in hospitals have a role that is not only limited to the pharmacy installation and management but also contributes to the Central Sterile Supply Department (CSSD) installation. The issue of sterilization and cleanliness of instruments and linen in hospitals is the responsibility of the CSSD to support the sustainability of quality services in hospitals. Although related to sterility, most of the staff of the installation CSSD in Indonesia are high school graduates with minimal health knowledge and are often transferred from other installations due to problems. Some hospitals combine CSSD with laundry; in contrast to the pharmacy installation, which actively involves pharmacists and pharmaceutical technical personnel, compliance with regulations and provisions is more highly respected compared to personnel in the CSSD installation.Objective: This study aims to analyze the application of transformational leadership style in CSSD installation in hospitals while highlighting the lack of leadership studies in pharmacy and the effectiveness of leadership in managing installation performance in hospitals with non-health personnel.Methods: The methods used include direct observation, interviews, and questionnaires with samples consisting of installation leaders and staff CSSD in hospitals. We explore the factors influencing and challenges faced in implementing transformational leadership in a hospital CSSD environment.Results: The questionnaire results showed that the transformational leadership scores of the leaders were high, and most employees were satisfied with the implementation of transformational leadership. Some management concepts have been applied to improve performance, but many have not been able to provide change due to a lack of response from employees.Conclusion: A leader in CSSD installation must be flexible in adopting a leadership style that suits the situation and conditions; the application of leadership style must consider internal factors such as human resources quality and organizational structure as well as external factors that are hospital management and budget support.